Functional Status of Stroke Patients at Neurologic Outpatient Clinic Dr. Hasan Sadikin General Hospital - Lee Shok Chen; Marina A. Moeliono; Lisda Amalia (Althea Medical Journal, 2016)
Background: Functional status refers to the ability of an individual to perform normal daily activity required to meet basic needs, fulfill usual roles, and maintain health and well-being. The objective of this study was to evaluate the level of disability and independency of stroke patients who had undergone rehabilitation therapy as the routine activity using Instrumental Activity of Daily Living (IADLs) and basic Activity of Daily Living (BADLs). Methods: This descriptive study carried out from September to October 2014 at Neurologic outpatient clinic Dr. Hasan Sadikin General Hospital Bandung with a total 33 subjects. Barthel index and IADLs questionnaire was used as an instrumental tool. Barthel index was used to measure the level of disability and IADLs was used to measure the level of independency of an individual.Results: From the 33 patients, 20 patients completed their rehabilitation therapy; 5 patients showed a moderate disability and 15 patients showed a mild disability at the Barthel Index of ADLs. The result of IADLs showed that 7 patients who completed the therapy had moderate level of independency, and 3 patients were at the category of high level of independency.Conclusions: Most of the stroke patients have moderate disability in Barthel Index and had low level of independency in IADLs. [AMJ.2016;3(1):126–31] DOI: 10.15850/amj.v3n1.720